Neonatal Outcomes of Pre gestational And Gestational Diabetes Mellitus - Faten Alaa Jaafar/ Mohammed Jalil Alwan/ Essam Kadhim Ibraheem ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2021)
Diabetes in pregnancy is associated with an increased risk of complications in both mother and fetus. Our study aims to analyze the neonatal complications of pre gestational diabetes mellitus PGDM as opposed to gestational diabetes mellitus GDM. Patient and methods: This cross sectional study included 70 pregnancies with diabetes mellitus among 2873 women admitted to the department of Obstetrics and Gynecology in Al-Khadhimya Teaching Hospital between the first of January to the first of July 2010, the mothers were divided in to PGDM mothers group and GDM mothers group. Data was collected by questionnaires. Results: the percentage of neonatal complications in PGDM were ; (15.6%) congenital anomalies, (18.8%) respiratory distress syndrome, (25%) hypoglycemia, (6.3%) neonatal jaundice, (12.5%) macrosomia, (0%) polycythemia, (3.1%) hypocalcemia, (6.3%) prematurity, (9.4%) perinatal mortality rate. In infant of GDM the complications were ; (0%) congenital anomalies, (2.6%) respiratory distress syndrome, (26.3%) hypoglycemia, (15.8%) neonatal jaundice, (13.2%) macrosomia, (5.3%) polycythemia, (2.6%) hypocalcemia, (13.2%) prematurity, (5.3%) perinatal mortality rate. The percentage of maternal pregnancy induced hypertension PIH was significantly higher in PGDM (43.8%) than GDM (21.1%), the P. value was (0.04). There is a significant risk of PGDM than the GDM in regarding to the congenital anomalies and respiratory distress syndrome, P. value was 0.011, 0.025 respectively. Conclusions: The percentage of maternal and neonatal complications was higher in PGDM than GDM, so strict control of blood glucose level during pregnancy and education of the diabetic women is essential before and during gestation.